Effect of hydrocortisone presence in aggregates size in cyclodextrin aqueous solutions - Malvas, Ana Rita Paiva (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014